Adherencia a multimicronutrientes y factores asociados en niños de 6 a 35 meses de sitios centinela, Ministerio de Salud, Perú - Munares-García, Oscar (2016)
ABSTRACT: Introduction: Anemia in children is a public health issue, and the current strategies include treatment and iron supplementation, but their level of adherence or compliance is unknown. Objective: To consider the adherence to multiple micronutrient powders and the associated factors. Methods: Epidemiological study of active surveillance through sentinel facilities in 2,024 children aged 6 to 35 months treated in health facilities of the Ministry of Health of Peru, from October to December 2014. Household visits were conducted in which counting of multiple micronutrient powders was applied and determined an adherence of consumption ≥ 90% envelopes, besides a form on the associated factors (anemia knowledge, iron-rich food, side effects, dosage regimen, drugs used, and motivation) was applied. Descriptive statistics, χ² test, Odds Ratio with a 95% confidence interval (CI), and binary logistic regression or adjusted Odds Ratio (aOR) were used. Results: Of all, 79.1% participants were aged 6 to 23 months; 75.9% received multiple micronutrient powders; and the adherence was equivalent to 24.4% (95%CI 22.3 - 26.6). The factors: continue supplementation (OR = 3.5; 95%CI 1.7 - 7.5); no nausea (OR = 3.0; 95%CI 2.0 - 4.3); no use of antibiotics (OR = 2.5; 95%CI 1.7 - 3.6); and intention to continue treatment (OR = 2.3; 95%CI 1.3 - 4.1) were associated with adherence. The variables: thought of continuing treatment (aOR = 2.6; 95%CI 1.1 - 6.1); presence of side effects, but no discontinuation of the treatment (aOR = 2.5; 95%CI 1.4 - 4.3); no use of antibiotics (aOR = 2.0; 95%CI 1.1 - 3.4); and belief that not only drugs cure anemia (aOR = 1.6; 95%CI 1.0 - 2.6) were associated in the multivariate analysis. Conclusion: There was a low prevalence of adherence to a demanding cut-off point (≥ 90% of envelopes of multiple micronutrient powders), and the associated factors are associated with absence of infections, side effects, and mother's beliefs.